`e^(2x) - 5e^x + 6 = 0` Solve the exponential equation algebraically. Approximate the result to three decimal places.

Textbook Question

Chapter 3, 3.4 - Problem 40 - Precalculus (3rd Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

`(e^x)^2-5e^x+6=0`

Put `e^x=t`

`t^2-5t+6=0`

`t^2-3t-2t+6=0`

`t(t-3)-2(t-3)=0`

`(t-2)(t-3)=0`

`t=2 and t=3`

`e^x=2 and e^x=3.`

`x=ln2 and x=ln3.`

`x=0.693 and x=1.099`

We’ve answered 318,936 questions. We can answer yours, too.

Ask a question